2015
DOI: 10.1108/jadee-04-2013-0015
|View full text |Cite
|
Sign up to set email alerts
|

Demand for organic produce

Abstract: Purpose -The differentiation that takes place in the Trinidad market only classifies tomatoes on the basis of its size. Farmers in many countries have been making an effort at agronomic differentiation strategies in order to receive better incomes. The purpose of this paper is to determine Trinidadian consumers' willingness to pay (WTP) and the market potential for organic tomatoes when marketed as a differentiated product. Design/methodology/approach -A survey research methodology was used in this study. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…This could be because women are more knowledgeable about food safety and are in charge of food and nutrition in the household, especially in developing countries. This supports the findings of Narine et al (2015), that being a female enhances WTP for organic food.…”
Section: Determinants Of Consumers' Willingness To Pay For Organic Beanssupporting
confidence: 90%
See 2 more Smart Citations
“…This could be because women are more knowledgeable about food safety and are in charge of food and nutrition in the household, especially in developing countries. This supports the findings of Narine et al (2015), that being a female enhances WTP for organic food.…”
Section: Determinants Of Consumers' Willingness To Pay For Organic Beanssupporting
confidence: 90%
“…The logistic regression model was used to investigate the driving factors of the buyers' WTP for organic beans. This was used because the decision to pay for organic beans was dichotomous and it has been employed in previous studies (Narine et al 2015;Oyawole et al 2016;Xu et al 2018). The explanatory variables in the model were selected based on previous studies on WTP (Falola 2014;Narine et al 2015;Owusu and Anifori 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiated products fulfill the same basic function relative to conventional products, but have different attributes such as type, style, quality, reputation, appearance, and location (Álamo, 2012). Over the past decades, researchers have devoted considerable efforts to understanding consumer preferences and WTP for differentiated products, including those produced locally (Gil et al, 2000;Loureiro and Hine, 2002;Darby et al, 2008;Printezis and Grebitus, 2020), friendly to the environment (McCluskey and Loureiro, 2003;Jensen et al, 2004;Oh et al, 2015), organic (Loureiro and Hine, 2002;James et al, 2009;Janssen and Hamm, 2012;Narine et al, 2015;Katz et al, 2019), in compliance with fair trade (McCluskey and Loureiro, 2003;Didier and Lucie, 2008), with traceability (Loureiro and Umberger, 2007;Abidoye et al, 2011;Zhang et al, 2012), of better quality (Hsu et al, 2009;Wann et al, 2018), supporting animal welfare (Bennett, 1996;Olynk et al, 2010;Clark et al, 2017), and free of genetically modified organisms (Loureiro and Hine, 2002). However, despite the contribution of prior studies on differentiated products in agriculture, more research needs to be conducted in the Caribbean to better understand consumer WTP for cow's milk that is produced in an eco-friendly manner and follows animal welfare standards that support sustainable dairy production.…”
Section: Introductionmentioning
confidence: 99%
“…In the Caribbean, to our knowledge, the literature on these products is limited. Narine et al (2015) estimated consumer WTP for organic tomatoes in Trinidad. They found that consumers are willing to pay a 20% premium for organic tomatoes.…”
Section: Introductionmentioning
confidence: 99%